Penyuluhan tentang penanganan udem pada kaki dan kecemasan pada ibu hamil trimester III di Puskesmas Air Dingin Padang - Rini Rahmayanti; Delvi Hamdayani; Yaumul Rhama Saputra; Ria Utami Yuliani; Darmaji Efrad (UII, 2020)
The risk of pregnancy is quite anxious for pregnant women, although it is known that physical and psychological changes will occur in the pregnancy process. These physical changes are in the form of increased hormones which can also affect a person's mood, back pain, leg cramps or tingling, and swollen feet that often occur at night and interfere with the quality of sleep of pregnant women. The purpose of this activity is to provide knowledge to pregnant women about edema and anxiety in the 3rd trimester and complementary therapies that can be done. This activity is carried out by the method of lectures, discussions and demonstrations. This activity was held on October 10, 2019 and was attended by 22 pregnant women. The results obtained were an increase in the knowledge, understanding, and ability of participants in understanding the material presented in this service activity. It was found that 80% of the audience present were able to mention the meaning of foot edema and anxiety, 75% of the audience present were able to mention and demonstrate how to soak feet in warm water. Health education can be carried out by health workers to increase the knowledge of pregnant women about edema and anxiety and its handling.Resiko kehamilan cukup membuat resah ibu hamil, meskipun diketahui dalam proses kehamilan akan terjadi perubahan-perubahan fisik maupun psikologis. Perubahan fisik tersebut berupa peningkatan hormon yang juga dapat mempengaruhi suasana hati seseorang, sakit punggung, kram atau kesemutan kaki, dan kaki bengkak yang sering terjadi di malam hari dan mengganggu kualitas tidur ibu hamil. Tujuan kegiatan ini adalah memberikan pengetahuan kepada ibu hamil tetang udem dan kecemasan pada trimester III dan terapi komplementer yang dapat dilakukan, Kegiatan ini dilakukan dengan metode ceramah, diskusi dan demonstrasi. Kegiatan ini dilaksanakan pada tanggal 10 oktober 2019 dan diikuti oleh 22 orang ibu hamil. Didapatkan hasil adanya peningkatan pengetahuan, pemahaman, dan kemampuan peserta dalam memahami materi yang disampaikan pada kegiatan pengabdian ini. Didapatkan 80% Audiens yang hadir mampu menyebutkan pengertianudem kaki dan kecemasan, 75% Audiens yang hadir mampu menyebutkan dan mendemonstrasikan cara rendam kaki air hangat. Pendidikan kesehatan ini dapat dilakukan oleh tenaga kesehatan untuk meningkatkan pengetahuan ibu hamil tentang udem dan kecemasan serta penanganannya. Kata Kunci : Udem, Kecemasan, Ibu Hamil, Trimester III ABSTRACTThe risk of pregnancy is quite anxious for pregnant women, although it is known that physical and psychological changes will occur in the pregnancy process. These physical changes are in the form of increased hormones which can also affect a person's mood, back pain, leg cramps or tingling, and swollen feet that often occur at night and interfere with the quality of sleep of pregnant women. The purpose of this activity is to provide knowledge to pregnant women about edema and anxiety in the 3rd trimester and complementary therapies that can be done. This activity is carried out by the method of lectures, discussions and demonstrations. This activity was held on October 10, 2019 and was attended by 22 pregnant women. The results obtained were an increase in the knowledge, understanding, and ability of participants in understanding the material presented in this service activity. It was found that 80% of the audience present were able to mention the meaning of foot edema and anxiety, 75% of the audience present were able to mention and demonstrate how to soak feet in warm water. Health education can be carried out by health workers to increase the knowledge of pregnant women about edema and anxiety and its handling.Keywords : Udem, Anxiety, Pregnant Women, 3rd Trimester